Evaluation of collapse mechanisms in masonry buildings: critical overview and case histories - Di Tommaso, Angelo; Casacci, Susanna (Alternativas, 2017)
In recent years the approach to the analysis of seismic vulnerability of masonry buildings considers as crucial the evaluation of potential local mechanisms. The “fracture” lines depicted on the wall (when it is “compact”) can show its labile condition of equilibrium and point out the potential kinematic of relative motion among blocks. The analytical evaluation of kinematics, linear and non-linear, presents some aspects that could be analysed with criticism. Among the techniques to contrast the potential mechanisms some very effective ones could be considered: plating with composites (covered by plaster) or reinforced re-pointing. Basic criteria to apply it and analytical procedures to determine the level of upgrading are considered in detail. This paper will analyse some of these aspects with reference to actual cases of study (Pavarotti theatre and San Barnaba Church in Modena, and campanile in Reno Centese, Ferrara, Italy).